2012
DOI: 10.1016/j.joen.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-reported History of Endodontic Treatment in the Baltimore Longitudinal Study of Aging

Abstract: Introduction Self-reported history of endodontic treatment (SRHET) has been used as a simplified method to estimate history of endodontic disease and treatment. This study aimed to quantify the validity of SRHET, as reported in the Baltimore Longitudinal Study of Aging (BLSA), as a method to: 1- identify individuals who experienced endodontic treatment (ET); and 2- identify individuals who present with apical periodontitis (AP). Methods SRHET was collected through the BLSA questionnaire in 247 participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The use of SROH measures provides relevant cost and time savings in large epidemiological surveys. 19,21 SROH is a known Likert-type scale and previous studies have provided consistent evidence of the construct validity of this model. 19,23 Limitations of the SROH approach must be clarified.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The use of SROH measures provides relevant cost and time savings in large epidemiological surveys. 19,21 SROH is a known Likert-type scale and previous studies have provided consistent evidence of the construct validity of this model. 19,23 Limitations of the SROH approach must be clarified.…”
Section: Discussionmentioning
confidence: 65%
“…In the last years, self-reported oral health (SROH) status has been increasingly implemented in dentistry. [18][19][20][21] Few studies have tested the relationship between clinical scores of CAB and oral health in humans. The current study tested this association in a group of southern Brazilian patients using a SROH approach, 19 supplemented by an oral clinical examination measuring the number of teeth.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study conducted by Gomes et al found that self‐reported history of ET had 92% sensitivity, 89% specificity, 82% positive predictive value, and 95% negative predictive value compared to panoramic radiographs . Both studies concluded that self‐reported ET is a highly accurate method to predict historic ET …”
Section: Discussionmentioning
confidence: 98%
“…Pitiphat et al found that self‐reported history of root canal treatment had 90% sensitivity, 94% specificity, a positive predictive value of 86%, and a negative predictive value of 95% compared to clinical and radiograph examinations . A more recent study conducted by Gomes et al found that self‐reported history of ET had 92% sensitivity, 89% specificity, 82% positive predictive value, and 95% negative predictive value compared to panoramic radiographs . Both studies concluded that self‐reported ET is a highly accurate method to predict historic ET …”
Section: Discussionmentioning
confidence: 99%
“…As discussed extensively in previous studies (Gomes et al . , ), another consideration is related to the radiographic analysis and its inherent limitations, particularly for the detection of AP. The cross‐sectional radiologic detection of AP does not provide information on the activity of the disease.…”
Section: Discussionmentioning
confidence: 99%